2022
DOI: 10.1039/d1ee03131g
|View full text |Cite
|
Sign up to set email alerts
|

Air-processable high-efficiency CISSe solar cells from DMF molecular solution and their application to perovskite/CISSe tandems

Abstract: A breakthrough in the N,N-dimethylformamide (DMF) molecular ink route for fabricating highly efficient, low bandgap CuIn(S,Se)2 (CISSe) solar cells is presented, demonstrating a newly certified record efficiency of 14.4% from...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…On the other hand, 4T perovskite/CZTS also showed promising PCE above 22% on the rigid substrates. 79,184 Overall, these tandem PCEs already exceeded the PCEs of the single-junction solar cell itself, with the most promising PCE on perovskite/CIGS tandem on rigid and flexible devices. Interestingly, based on the finding strategies on perovskite/Si tandem, the practical PCE of perovskite/CIGS could realistically be achieved at around 32%.…”
Section: Cuch-based Tandem Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 4T perovskite/CZTS also showed promising PCE above 22% on the rigid substrates. 79,184 Overall, these tandem PCEs already exceeded the PCEs of the single-junction solar cell itself, with the most promising PCE on perovskite/CIGS tandem on rigid and flexible devices. Interestingly, based on the finding strategies on perovskite/Si tandem, the practical PCE of perovskite/CIGS could realistically be achieved at around 32%.…”
Section: Cuch-based Tandem Solar Cellsmentioning
confidence: 99%
“…Several attempts have been made to develop various ternary-CIS compounds as photoactive materials for solar cells. 9,78–82 To form a ternary system, additional transition metals or metalloids (such as Sb, Bi, Sn, In, Fe, Ag, etc. ) need to be added to the binary system (CuS/Se).…”
Section: Ternary Cuch-based Solar Cellsmentioning
confidence: 99%
“…But, all device parameters, V oc , short-circuit current density (J sc ), and fill factor (FF), were lower compared to the devices made by using a vacuum-based process. 8,13,19 We have developed spray pyrolysis with deionized water (DIW) for Cu(In,Ga)(S,Se) 2 (CIGSSe) solar cells. 16,17,20−23 DIW is the most eco-friendly, low-cost solvent, and it does not retain any kind of carbon residue in the fabricated absorber, which is usually observed when using organic solvents and can be a possible limitation to device performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a non-hydrazine solution, Uhl et al used dimethyl sulfoxide (DMSO) solvent-based ink solution containing Cu, In (chloride-based), and thiourea and fabricated 13.0% efficient CISe solar cell . Siddique et al reported 14.4% CuIn­(S,Se) 2 (CISSe) cell using N , N -dimethylformamide (DMF) molecular ink . With air annealing, they obtained improved crystallinity of the CISSe absorber without carbon residue near the bottom electrode, which enabled a PCE of more than ∼14%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation